Telomere length: lights and shadows on their role in human reproduction. Issue 2 (1st October 2018) - Rocca, Maria Santa; Foresta, Carlo; Ferlin, Alberto
Abstract: Telomeres are repeated DNA sequences whose main function is to preserve genome stability, protecting chromosomes ends from shortening caused by progressive loss during each cell replication or DNA damage. Telomere length regulation is normally achieved by telomerase enzyme, whose activity is progressively shut off during embryonic differentiation in somatic tissues, whereas it is maintained in germ cells, activated lymphocytes, and certain types of stem cell populations. The maintenance of telomerase activity for a longer time is necessary for germ cells to delay telomere erosion, thus avoiding chromosome segregation defects that could contribute to aneuploid or unbalanced gametes. Over the last few years, telomere biology has become an important topic in the field of human reproduction, encouraging several studies to focus on the relation between telomere length and spermatogenesis and male fertility, embryo development and quality during assisted reproductive treatment, and female pathologies as polycystic ovary, premature ovarian insufficiency, and endometriosis. This review analyzes whether telomere length in germ cells is related to reproduction fitness, whether telomere length is related to pathologies associated with male and female fertility, and whether measurement of telomere length could represent a biomarker of germ cell and embryo quality. Telomere length could be considered a molecular marker of spermatogenesis and sperm quality and is somewhat related to male fertility potential. Fewer evidence, although promising, is available for oocytes, female (in)fertility, and embryo quality. The increasing evidence for a role of telomeres and telomere length in human reproduction, indeed, has expanded the historical view of considering them just a marker of aging. Telomere length might have in the future a prognostic potential in couple infertility, especially useful to select best germ cells with the greatest potential of fertilization. Abstract : Telomere length could be considered a molecular marker of spermatogenesis and sperm quality and is somewhat related to male fertility potential. Fewer evidence, although promising, is available for oocytes, female (in)fertility, and embryo quality.